2017
DOI: 10.1111/edt.12338
|View full text |Cite
|
Sign up to set email alerts
|

Histological assessment of regenerative endodontic treatment in animal studies with different scaffolds: A systematic review

Abstract: Background/aim: The concept of regenerative endodontic procedures remains con-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 47 publications
(172 reference statements)
1
28
0
5
Order By: Relevance
“…Another study revealed that hDPSCs combined with NF-SMS were used to fill the pulp cavity and form pulp-like tissues similar to native pulp in a rat model [8]. However, true regeneration of DPC has not been achieved in RE [914]. To improve the outcomes of RE, a key issue is to improve DPSC function in dental clinic conditions; therefore, it is necessary to explore the mechanisms controlling the directed differentiation of DPSCs in these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Another study revealed that hDPSCs combined with NF-SMS were used to fill the pulp cavity and form pulp-like tissues similar to native pulp in a rat model [8]. However, true regeneration of DPC has not been achieved in RE [914]. To improve the outcomes of RE, a key issue is to improve DPSC function in dental clinic conditions; therefore, it is necessary to explore the mechanisms controlling the directed differentiation of DPSCs in these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The currently applied regenerative endodontic procedures (REP) comprise the induction of a blood clot, causing both the release of sequestered growth factors and the attraction of endogenous (stem) cells, such as stem cells from the apical papilla (SCAPs) [ 2 , 3 ]. However, in addition to the questionable histological nature of the regenerated tissues [ 4 , 5 ], adequate pulp tissue revascularization is an often recurring concern in cell homing-based approaches given the limited vascular access through the apical foramen [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The literature also points out that the risk of intracanal calcification after REPs was higher in cases medicated with calcium hydroxide (76.9%) compared with teeth medicated with antibiotic pastes (46.2%) [32] Altai et al [33] in a comprehensive review highlighted that all the studies that used MTA directly on blood clot or on other scaffolds showed intracanal calcification. Correspondingly, other case reports have shown the formation of hard tissue bridges under MTA, and scattered calcification inside the canal, when some portion of the MTA was pushed into the canal.…”
Section: Discussionmentioning
confidence: 99%